(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The term "Ancient India" refers to the Indian Subcontinent spanning from prehistoric times until the conclusion of the Gupta Empire around 500 CE. A profound statement by A.S. Altekar likens knowledge to the "third eye" of humanity, offering insights into all matters and guiding actions. In the spiritual realm, knowledge leads to salvation, while in the secular realm, it propels comprehensive advancement and prosperity. Education’s illuminating influence dispels illusions, overcomes challenges, and unveils life’s authentic values. The significance of knowledge and education in ancient India is exemplified by the Vedas, where the very essence of the term signifies knowledge. This paper delves into a descriptive exploration of the concept and establishment of Higher Education in Ancient India, organized into three principal categories: Vedic Education, Brahminical Education, and Buddhist Education.